Genotyping and study of the pauA and sua genes of Streptococcus uberis isolates from bovine mastitis. - Perrig, Melina Soledad (2015)
This study aimed to determine the clonal relationship among 137 Streptococcus uberis isolates from bovine milk with subclinical or clinical mastitis in Argentina and to assess the prevalence and conservation of pauA and sua genes. This information is critical for the rational design of a vaccine for the prevention of bovine mastitis caused by S. uberis. The isolates were typed by random amplified polymorphic DNA (RAPD) analysis and by pulsed-field gel electrophoresis (PFGE). The 137 isolates exhibited 61 different PFGE types and 25 distinct RAPD profiles. Simpson's diversity index was calculated both for PFGE (0.983) and for RAPD (0.941), showing a high discriminatory power in both techniques. The analysis of the relationship between pairs of isolates showed 92.6% concordance between both techniques indicating that any given pair of isolates distinguished by one method tended to be distinguished by the other. The prevalence of the sua and pauA genes was 97.8% (134/137) and 94.9% (130/137), respectively. Nucleotide and amino acid sequences of the sua and pauA genes from 20 S. uberis selected isolates, based on their PFGE and RAPD types and geographical origin, showed an identity between 95% and 100% with respect to all reference sequences registered in GenBank. These results demonstrate that, in spite of S. uberis clonal diversity, the sua and pauA genes are prevalent and highly conserved, showing their importance to be included in future vaccine studies to prevent S. uberis bovine mastitis.